Struktur Epistemologi Tafsir al-Tibyan fi Tafsir Ayat al-Ahkam Karya Achmad Nasrullah Abdurrochim Tambakberas, Jombang - Khoirur Rifqi Robiansyah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Kitab al-Tibyan fi Tafsir Ayat al-Ahkam min al-Qur'an by K.H. Achmad Nasrullah Abdurrochim added to the treasures of books of interpretation of Ahkam by Nusantara scholars whose existence was still minimal. This book was written when Nasrullah encountered many cases when he was a judge at the Jombang District Court. In addition, he is also a kiyai who actively takes care of the pesantren in Tambakberas, Jombang. It is interesting to examine whether the book of interpretation produced by combining two backgrounds, namely kiyai pesantren and legal practitioners in religious courts, does it produce a more contextual pattern of ahkam interpretation and provides answers to socio-religious problems that are practically faced in society. The epistemology of interpretation is the main study in this article to find out how the sources, methods, approaches, procedures and validity of interpretation are. The method used in this research is descriptive analysis using the book al-Tibyan fi Tafsir Ayat al-Ahkam min al-Qur'an as the primary source. Meanwhile, to test the validity of using the theory of coherence, correspondence and pragmatism. Finally, this article shows that Nasrulloh in his interpretation prefers historical sources over his own opinion. The method he uses is maudhu'i which is dominant in discussing the theme of marriage. The procedure for his interpretation first explains the vocabulary of the verse, then the asbabul nuzul, then he interprets the verse with a question and answer model, then ends with a conclusion. As for the validity, all aspects of validity theory are applied in its interpretation.